Engineered Fibroblast Extracellular Vesicles Attenuate Pulmonary Inflammation and Fibrosis in Bleomycin-Induced Lung Injury - Ibrahim, Abdulrahman; Ciullo, Alessandra; Li, Chang; Akhmerov, Akbarshakh; Peck, Kiel; Jones-Ungerleider, K. C.; Morris, Ashley; Marchevsky, Alberto; Marbàn, Eduardo; Ibrahim, Ahmed Gamal (Frontiers in Cell and Developmental Biology, 2021)
Pulmonary fibrosis is a progressive disease for which no curative treatment exists. We have previously engineered dermal fibroblasts to produce extracellular vesicles with tissue reparative properties dubbed activated specialized tissue effector extracellular vesicles (ASTEX). Here we investigate the therapeutic utility of ASTEX in vitro and in a mouse model of bleomycin-induced lung injury. RNA sequencing demonstrates that ASTEX are enriched in micro RNAs (miRs) cargo compared to EVs from untransduced dermal fibroblast EVs (DF-EVs). Treating primary macrophages with ASTEX reduced IL6 expression and increased IL10 expression compared to DF-EVs-exposed macrophages. Furthermore, exposure of human lung fibroblasts or vascular endothelial cells to ASTEX reduced expression of smooth muscle actin, a hallmark of myofibroblast differentiation (respectively). In vivo, intratracheal administration of ASTEX in naïve healthy mice demonstrated a favorable safety profile with no changes in body weight, lung weight to body weight, fibrotic burden, or histological score three weeks post-exposure. In an acute phase (short-term) bleomycin model of lung injury, ASTEX reduced lung weight to body weight, IL6 expression, and circulating monocytes. In a long-term setting, ASTEX improved survival and reduced fibrotic content in lung tissue. These results suggest potential immunomodulatory and anti-fibrotic properties of ASTEX in lung injury.